2021
DOI: 10.1007/s11104-021-05077-7
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration dynamics in fragmented landscapes at the leading edge of distribution: Quercus suber woodlands as a study case

Abstract: Aims We studied the regeneration dynamics of woodlands and abandoned old fields in a landscape dominated by Quercus suber in its lower limits of rainfall and temperature. Two hypotheses were established: (1) regeneration of Quercus species is strongly favored by the presence of tree cover; and (2) growth of Q. suber is driven by the climatic variables that represent the lower ecological limit of its leading distribution edge. Methods We selected woodlands … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…The lower acorn availability in stand B may be due to a lower tree density (Acácio et al, 2007). The results obtained in this study for cork oak forest systems in Northern Portugal are in accordance with trends reported in southern Portugal (Algarve and Alentejo provinces) and in the North subdivision of the Central plateau of the Iberian Peninsula (Salamanca province), where dense stands have shown a greater supply of acorns and a higher density of seedlings (Acácio et al, 2007;Montero-Muñoz et al, 2021;Ritsche et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The lower acorn availability in stand B may be due to a lower tree density (Acácio et al, 2007). The results obtained in this study for cork oak forest systems in Northern Portugal are in accordance with trends reported in southern Portugal (Algarve and Alentejo provinces) and in the North subdivision of the Central plateau of the Iberian Peninsula (Salamanca province), where dense stands have shown a greater supply of acorns and a higher density of seedlings (Acácio et al, 2007;Montero-Muñoz et al, 2021;Ritsche et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the species occurrence in the early 20th century is not detailed and widely referenced; thus, the comparison with the actual range is hard to assess. However, we can assume that variation in the distribution in a century is not significant for a long-life tree, such as cork oak, so the responses to climate change can be stated by recent investigations about tree dieback and changes in regeneration processes [56][57][58][59]. However, we can presently deal with advanced remote sensing techniques, which are useful to obtain punctual and refined data; by coupling that information with indexes, such as Emberger's Index, it is finally possible to monitor the responses of forest species to variations in climate, at least for the next century.…”
Section: Discussionmentioning
confidence: 99%